2017
DOI: 10.1103/physreve.96.012320
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nonstationary transition to synchronized states of a neural network using recurrence analyses

Abstract: We study the stability of asymptotic states displayed by a complex neural network. We focus on the loss of stability of a stationary state of networks using recurrence quantifiers as tools to diagnose local and global stabilities as well as the multistability of a coupled neural network. Numerical simulations of a neural network composed of 1024 neurons in a small-world connection scheme are performed using the model of Braun et al. [Int. J. Bifurcation Chaos 08, 881 (1998)IJBEE40218-127410.1142/S0218127498000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…Regarding complex networks, it is known that this kind of system can show emergent behavior, where the global behavior observed is richer than the sum of the individual element behaviors. In this way, the existence of non-monotonic transitions to synchronization as a function of coupling strength in neural networks [26][27][28][29][30], where non-stationary states can be noticed, has been reported in the literature. In some cases, in the transition region, on-off intermittency in the two states has been observed, where the network displays the existence of two locally stable states but globally unstable ones [18,26], as defined in [31].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Regarding complex networks, it is known that this kind of system can show emergent behavior, where the global behavior observed is richer than the sum of the individual element behaviors. In this way, the existence of non-monotonic transitions to synchronization as a function of coupling strength in neural networks [26][27][28][29][30], where non-stationary states can be noticed, has been reported in the literature. In some cases, in the transition region, on-off intermittency in the two states has been observed, where the network displays the existence of two locally stable states but globally unstable ones [18,26], as defined in [31].…”
Section: Introductionmentioning
confidence: 79%
“…In this way, the existence of non-monotonic transitions to synchronization as a function of coupling strength in neural networks [26][27][28][29][30], where non-stationary states can be noticed, has been reported in the literature. In some cases, in the transition region, on-off intermittency in the two states has been observed, where the network displays the existence of two locally stable states but globally unstable ones [18,26], as defined in [31]. In [9], the dynamical properties regarding synchronization and transition characteristics are studied as a function of the connection architecture, with both small-world and random topologies being considered.…”
Section: Introductionmentioning
confidence: 79%
“…It was shown that the scale-free network displays a non-monotonic evolution of the phase synchronization as the coupling between neurons increases. A similar scenario has been observed in small-world networks, which is called "anomalous phase synchronization" [30,31,55], since the traditional behavior should monotonically transition to PS [33]. Especially, Parkinson's disease and some episodes of seizure behavior generated by epilepsy may be associated to anomalous synchronization.…”
Section: Discussionmentioning
confidence: 52%
“…For the interval of coupling strength 0.002 < ε < 0.007, the network exhibited a local maximum of phase synchronization (ε ≈ 0.004). This behavior was also observed in small-world network [30,31,51], which characterized a non-monotonic evolution of the synchronization level as a function of the coupling that could be understood as an abnormal synchronization since PS occurred for a coupling ε < ε * . In this way, it is known that several brain disorders, such as Parkinson's disease and autism, are related to abnormal neuronal synchronization [6][7][8][9], thus it is expected that the application of synchronization suppression methods may be useful to vanish the anomalous synchronization, as observed in Figure 2.…”
Section: Phase Synchronization Quantifiermentioning
confidence: 61%
See 1 more Smart Citation